MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN AL AZHAR 12 ISLAMIC JUNIOR HIGH SCHOOL RAWAMANGUN EAST JAKARTA - evitha soraya; Supadi Supadi (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
The purpose of this study was to determine the management of facilities and infrastructure as seen from the planning, procurement, and elimination of educational facilities and infrastructure in Al Azhar 12 Islamic Middle School, East Jakarta. This research was conducted in early January to January 2020. This study used a qualitative approach with descriptive methods. Data collection techniques are done by interview, observation, and study documentation. Sources of data from this study are the Principal, Deputy Principal, Facilities and Infrastructure Staff, Laboratory Staff of Natural Sciences. The results of the study concluded that; (1) planning educational facilities and infrastructure include: making needs analysis, setting priorities by holding work meetings (RAKER) in schools, preparing budgets, and ratifying the RAPBS, (2) procurement of educational facilities and infrastructure including: submitting a letter of request for procurement of goods to foundations, foundations and schools revisit the specifications of goods and available budgets, the purchasing department surveys the price of goods and makes purchase orders (PO) to suppliers, purchases vouchers, purchases, distributes goods, and (3) maintenance is self awareness respectively.